Free-space Optical Communication based on Augmentation of OAM Modes - DAI Weijie; SU Xiaofeng; LIU Xiaoqian; ZHANG Liyan; WEI Tiankuo; SONG Jian; DONG Yuhan (Guangtongxin yanjiu)
【Objective】Atmospheric and oceanic turbulence causes the mode fading of optical Orbital Angular Momentum (OAM), thus being one of the main factors that deteriorate the performance of OAM-based Free-Space Optical Communications (FSOC) systems. Anti-turbulence effect has long been a pursuit of researchers in the field of OAM-FSOC.【Methods】In the context of high-capacity optical wireless communication based on the OAM mode, turbulence causes symmetric diffusion of the OAM spectrum. Traditional turbulence mitigation schemes require complex wavefront sensing and combining solutions. However, in a partially coherent light field, the coexistence of twisted phase and vortex phase leads to an asymmetric diffusion behavior of the OAM spectrum, providing a new approach for turbulence mitigation. This work highlights the paradigm shift of information transmission inspired by asymmetrical OAM spectra, aiming to utilize the controllable asymmetry caused by the twist factor for mode augmentation. Based on this, we further propose novel mode encoding scheme at the transmitter and mode combining scheme at the receiver. The proposed schemes bring significant improvements in terms of the average capacity, aggregate capacity, and Bit Error Rate (BER) of OAM-FSOC systems.【Results】Numerical results show significant performance improvements consistent with theoretical predictions, including the actual capacity, capacity upper bound, and available link distance in turbulent channels, as well as the ability to suppress turbulence.【Conclusion】The proposed solution in the paper is not only the application of twisted partially coherent light fields in OAM-FSOC systems but also the utilization of the physical fact of controllable asymmetric diffusion of the OAM spectrum. The paper demonstrates the significant potential for the application of cutting-edge optical wave physics theories, exemplified by the regulation of twisted phase partially coherent light fields, in next-generation optical wireless communications.